Role of Topical Biological Therapies and Dressings in Healing Ischemic Wounds. (December 2018) - Orrapin, Saritphat; Rekasem, Kittipan
Ischemic wounds are the most severe expression of critical limb ischemia (CLI), and they have been defined clinically as an end stage of peripheral arterial disease. Urgent revascularization is a fundamental part for limb salvage in patients with CLI. However, the risk of revascularization should be weighed against the likelihood of success given a patient's life-threatening comorbidities. Once the condition of arterial insufficiency is revascularized, wound care is an important aspect to promote the wound healing process and infection control. MOIST concept for wound care is a modern systematic treatment for enhanced wound healing process. Currently, advanced biological therapies are emerging in ischemic wound therapies to restore the wound healing process and involve active biological agents to support the wound healing process. We studied and summarized the different types of available topical biological therapies and their mechanisms on the healing process including platelet-derived growth factor, epidermal growth factor, fibroblast growth factor, and vascular endothelial growth factor, platelet-rich plasma, and honey for local wound care of patient with CLI. Our review suggests that topical platelet-derived growth factor, epidermal growth factor, platelet-rich plasma, and honey are available as well as considered in the ischemic wound healing process enhancement through the MOIST concept. In conclusion, biologic wound dressing or topical agent therapy may improve the wound healing process, increase limb salvage, is inexpensive, and provides potential safety with nontoxic low-risk therapy in patients with an ischemic wound. Thus, local wound care by biological dressing should be added in adjuvant treatment for ischemic wound patients. However, further randomized studies are needed to support efficacy and long-term outcomes of these biological dressing in patients with ischemic wound.